Tahap kesakit an pos-operatif bagi pesakit yang menjalani surgeri 01 Hospital Universiti Sains Malaysia (HUSM) - Atiqah, Rosli (Universiti Sains Malaysia, 2008)
Pain is an unpleasant and highly personal experience that may be imperceptible to others. Pain exists when actual or potential tissue damage and this may associate unpleasant sensmy and personal emotional experience. This research is to detennine patienf s pain level after surgery and to detennine factors that related to individual pain level. Generally, this research is done to detennine patient's pain level after surgery at Hospital University Science Malaysia (HUSM). Specifically, the aim of this study to find is there any difference between pain level after surgery in 24 hours and pain level after surgery in 24-48 hours. Besides, this study is to detennine the correlation between pain level post operative with demographic factors which is sex, age and ethnic. This study is quantitative with sample coiiection from patients after surgery at HUSM. Surgical wards at HUSM are choosing as location in this study. The wards are in 2 Intan and 3 Utara. Sample was choosing randomly. Questionnaire was translated in Bahasa Melayu for easier to use as instrument. From results of this study, there is correlation between sex and pain level after surgery where as women have higher pain level than men. Although, in this study found that there is no correlation between age and pain level after surgery. Besides, correlation between ethnic and pain level after surgery can not be found because all samples in this study are Malays. Other than that, the difference between pain level after surgery in 24 hours and pain level after surgery in 24-48 hours is exist. Detennination is done in this study about correlation between demographic factors and post operative patient's pain level. At the same time, the difference between pain level after surgery in 24 hours and pain level after surgery in 24-48 hours also detennined.